Influence of study satisfaction on academic procrastination in psychology students: a preliminary study - Dominguez-Lara, Sergio Alexis (2017)
The aim of this predictive study was to analyze the degree of influence of study satisfaction (SS) on academic procrastination (AP). One hundred forty- eight (148) psychology students (111 women) between 18 and 32 years old (M = 22.41) were evaluated using the Brief Scale of Study Satisfaction and the Academic Procrastination Scale. After preliminary analyses focused on the scores reliability (α > 0.70) and correlations between dimensions, a regression analysis was performed to determine how much of the variability in the AP dimensions’ scores is explained by the variations in the SS. For that purpose, a method that uses bivariate correlations corrected for attenuation and provides confidence intervals under a bootstrap approach of the associated statistics was applied. All analyses were assessed from an effect size approach. The results indicate that the influence of SS on AP was not significant. These findings provide new ways to implement studies in order to understand the procrastinating behavior in the university setting. DOI: https://doi.org/10.24265/liberabit.2017.v23n1.09